Molecular mechanisms of dysfunction of muscle fibres associated with Glu139 deletion in TPM2 gene. Issue 1 (December 2017) - Borovikov, Yurii; Rysev, Nikita; Karpicheva, Olga; Sirenko, Vladimir; Avrova, Stanislava; Piers, Adam; Redwood, Charles
Abstract Deletion of Glu139 in β-tropomyosin caused by a point mutation in TPM2 gene is associated with cap myopathy characterized by high myofilament Ca2+ -sensitivity and muscle weakness. To reveal the mechanism of these disorders at molecular level, mobility and spatial rearrangements of actin, tropomyosin and the myosin heads at different stages of actomyosin cycle in reconstituted single ghost fibres were investigated by polarized fluorescence microscopy. The mutation did not alter tropomyosin's affinity for actin but increased strongly the flexibility of tropomyosin and kept its strands near the inner domain of actin. The ability of troponin to switch actin monomers "on" and "off" at high and low Ca2+, respectively, was increased, and the movement of tropomyosin towards the blocked position at low Ca2+ was inhibited, presumably causing higher Ca2+ -sensitivity. The mutation decreased also the amount of the myosin heads which bound strongly to actin at high Ca2+ and increased the number of these heads at relaxation; this may contribute to contractures and muscle weakness.